Microsporidia: a new taxonomic, evolutionary, and ecological synthesis. Issue 8 (August 2022) - Bojko, Jamie; Reinke, Aaron W.; Stentiford, Grant D.; Williams, Bryony; Rogers, Martin S.J.; Bass, David
Abstract : Microsporidian diversity is vast. There is a renewed drive to understand how microsporidian pathological, genomic, and ecological traits relate to their phylogeny. We comprehensively sample and phylogenetically analyse 125 microsporidian genera for which sequence data are available. Comparing these results with existing phylogenomic analyses, we suggest an updated taxonomic framework to replace the inconsistent clade numbering system, using informal taxonomic names: Glugeida (previously clades 5/3), Nosematida (4a), Enterocytozoonida (4b), Amblyosporida (3/5), Neopereziida (1), and Ovavesiculida (2). Cellular, parasitological, and ecological traits for 281 well-defined species are compared with identify clade-specific patterns across long-branch Microsporidia. We suggest that future taxonomic circumscriptions of Microsporidia should involve additional markers (SSU/ITS/LSU), and that a comprehensive suite of phenotypic and ecological traits help to predict broad microsporidian functional and lineage diversity. Highlights: Microsporidian systematics has entered a genomic era, with ~38 species' genomes available to date, and this number is expected to double by the end of 2022. Minimal frameworks can unite microsporidian taxonomy, promoting global access to high-quality genetic/pathological data. We propose sequencing of the internal transcribed spacer (ITS), large-subunit (LSU) region, and small-subunit ribosomal RNA gene (SSU), in lieu of genomic data, when describing microsporidian taxa. Ecological parameters across formally described Microsporidia are synthesised, revealing astonishing ecological diversity, which is mapped to their phylogenetic clade-based higher taxonomy. We coalesce previous microsporidian taxonomic classifications with new-age clade-based systematics to draw parallels between classical taxonomic approaches for other organisms and the Microsporidia.